Legally a Lady. (August 2019) - Ingersoll, Hannah
In a period of ambiguous legal culture between the U.S. Civil War and the legal imposition of Jim Crow, court cases reveal Black women navigating race, class, and gender as they sought a seat in the Ladies' Car and claimed their right to dignity within American society.